The Potential Impact of "Take the Volume Pledge" on Outcomes After Carotid Artery Stenting. Issue 2 (15th March 2019) - Lopez Ramos, Christian; Brandel, Michael G; Rennert, Robert C; Hirshman, Brian R; Wali, Arvin R; Steinberg, Jeffrey A; Santiago-Dieppa, David R; Flagg, Mitchell; Olson, Scott E; Pannell, J Scott; Khalessi, Alexander A
Abstract: BACKGROUND: The "Volume Pledge" aims to centralize carotid artery stenting (CAS) to hospitals and surgeons performing ≥10 and ≥5 procedures annually, respectively. OBJECTIVE: To compare outcomes after CAS between hospitals and surgeons meeting or not meeting the Volume Pledge thresholds. METHODS: We queried the Nationwide Inpatient Sample for CAS admissions. Hospitals and surgeons were categorized as low volume and high volume (HV) based on the Volume Pledge. Multivariable hierarchical regression models were used to examine the impact of hospital volume (2005-2011) and surgeon volume (2005-2009) on perioperative outcomes. RESULTS: Between 2005 and 2011, 22 215 patients were identified. Most patients underwent CAS by HV hospitals (86.4%). No differences in poor outcome (composite endpoint of in-hospital mortality, postoperative neurological or cardiac complications) were observed by hospital volume but HV hospitals did decrease the likelihood of other complications, nonroutine discharge, and prolonged hospitalization. From 2005 to 2009, 9454 CAS admissions were associated with physician identifiers. Most patients received CAS by HV surgeons (79.2%). On multivariable analysis, hospital volume was not associated with improved outcomes but HV surgeons decreased odds of poor outcome (odds ratio [OR] 0.76, 95% confidence interval [CI] 0.59-0.97; P  = .028), complications (OR 0.56, 95% CI 0.46-0.71, P  < .001), nonroutine discharge (OR 0.70, 95% CI 0.57-0.87; P  = .001), and prolonged hospitalization (OR 0.52, 95% 0.44-0.61, P  < .001). CONCLUSION: Most patients receive CAS by hospitals and providers meeting the Volume Pledge threshold for CAS. Surgeons but not hospitals who met the policy's volume standards were associated with superior outcomes across all measured outcomes.